2021
DOI: 10.1101/2021.01.08.425868
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards the restoration of ancient hominid craniofacial anatomy: Chimpanzee morphology reveals covariation between craniometrics and facial soft tissue thickness

Abstract: In modern humans, facial soft tissue thicknesses have been shown to covary with craniometric dimensions. However, to date it has not been confirmed whether these relationships are shared with non-human apes. In this study, we analyze these relationships in chimpanzees (Pan troglodytes) with the aim of producing regression models for approximating facial soft tissue thicknesses in Plio-Pleistocene hominid individuals. Using CT scans of 19 subjects, 637 soft tissue, and 349 craniometric measurements, statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 60 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…Given that chimpanzee and modern human means differ significantly, it is not possible to approximate the position of pronasale for these species using averages. More and more forensic studies are revealing that linear regression models actually outperform averages (Campbell et al, 2021a;Dinh et al, 2011) Based on the results of the out-of-group interspecies compatibility tests, we suggest that it can be formulated as a general rule that hominids with longer cranial base lengths tend to have longer nasal cavities, and that hominids with maxillae tilted further down from the Frankfurt horizontal plane tend to have axes of the nasal cavity also directed further downwards. Furthermore, since this has been identified in two extant species of hominid, which feature quite distinct skull morphologies, and that the regression models can reliably approximate pronasale position and nasal protrusion in other African great apes (i.e.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Given that chimpanzee and modern human means differ significantly, it is not possible to approximate the position of pronasale for these species using averages. More and more forensic studies are revealing that linear regression models actually outperform averages (Campbell et al, 2021a;Dinh et al, 2011) Based on the results of the out-of-group interspecies compatibility tests, we suggest that it can be formulated as a general rule that hominids with longer cranial base lengths tend to have longer nasal cavities, and that hominids with maxillae tilted further down from the Frankfurt horizontal plane tend to have axes of the nasal cavity also directed further downwards. Furthermore, since this has been identified in two extant species of hominid, which feature quite distinct skull morphologies, and that the regression models can reliably approximate pronasale position and nasal protrusion in other African great apes (i.e.…”
Section: Discussionmentioning
confidence: 91%
“…Recently, Campbell et al (2021a) showed that facial soft tissue thicknesses covary with craniometric dimensions in chimpanzees. However, Campbell et al (2021a) only analyzed . CC-BY 4.0 International license perpetuity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations